ECONOMETRIC MODELLING OF REGIONAL INDUSTRIAL ENTERPRISE STRUCTURE: THEORETICAL FOUNDATIONS AND EMPIRICAL EVIDENCE FROM KASHKADARYA REGION, UZBEKISTAN (American Journal of Business Management, Economics and Banking, 2026)
This article examines the theoretical foundations and empirical evidence of econometric modelling of regional industrial enterprise structure, drawing on the case of Kashkadarya Region, Uzbekistan. Using panel data from 148 industrial enterprises over the period 2018–2023, we estimate a System Generalised Method of Moments (System GMM) dynamic panel model to identify the key determinants of total factor productivity (TFP). Our results confirm that investment in digitalisation (β = 0.341; p = 0.016) and export volume (β = 0.447; p < 0.001) are the strongest structural drivers of enterprise efficiency. We further document a Structural Shift Index (SSI) of 0.12 and an HHI of 1,850, indicating moderate and moderately concentrated market conditions, respectively. The findings provide a quantitative basis for formulating evidence-based industrial policy in transitional emerging economies.